CULTURAL RATIONALITY AND AFRICAN RELIGIOUS CULTURE: A Critical Anthropological and Theological Investigation towards Intercultural Dialogue - Appiah-Kubi, Francis (Asian Horizons, 2019)
The situation of the world today, as well as every culture’s vocation, calls for intercultural dialogue as a guiding concept, open to the future, when faced with the various interpretations of pluralism. From anthropological and theological perspectives, this article, after delving into an overview of the historic encounter between the African and the European cultures, seeks to drum home the significance of African religious cultural rationality; it stresses on how the ecclesiological paradigm for Africa, the Church Family of God, contributes to the appreciation of intercultural dialogue in the context of pluralism. The objective, then, is to evaluate dialogue’s potential within the integration of different cultures. The path of dialogue becomes possible and fruitful when based on the awareness of each individual’s dignity and of the unity of all people in a common humanity, aiming at sharing and building up together a common destiny.